The late Eocene-early Miocene El Maitén Belt evolution: Magmatic response to the changing subduction zone geodynamics - Fernández Paz, Lucía (2020)
Fil: Fernandez Paz, Lucía. Universidad de Buenos Aires, CONICET, Instituto de Estudios Andinos "Don Pablo Groeber" (IDEAN)